Feasibility and safety of bronchoscopic transparenchymal nodule access in canines: a new real-time image-guided approach to lung lesions - Silvestri, Gerard A.; Herth, Felix; Keast, Thomas; Rai, Lav; Gibbs, Jason; Wibowo, Henky; Sterman, Daniel H. (Chest, 2015)
The current approaches for tissue diagnosis of a solitary pulmonary nodule are transthoracic needle aspiration, guided bronchoscopy, or surgical resection. The choice of procedure is driven by patient and radiographic factors, risks, and benefits. We describe a new approach to the diagnosis of a solitary pulmonary nodule, namely bronchoscopic transparenchymal nodule access (BTPNA).
Available online 25 December 2015
Gesehen am 29.09.2020